Fantasmas no espelho: uma análise da estética gótica no filme Os outros (2001) através do conceito freudiano do infamiliar - Bertoldi, Mariana de Setta (Universidade Federal de São Carlos, 2019)
The present work aims to analyze how the movie The Others (2001), by Alejandro Amenábar, integrates and modernizes itself on the Freudian concept of Uncanny in the cinematic tradition of the gothic. The Uncanny is part of a sensitivity core, something that is awakened on the individual something that is awakened in the individual when they are confronted with a situation that diverges from their conscious understanding of the world. Gothic art, by transposing into the environment the psychological and emotional state of the individual, transforms into Uncanny what was once familiar, becoming the genre that best suits the Freudian concept. In addition, the gothic is responsible for the reflection of social trauma, a repressed essence that returns after being left in the shadows.
Ghosts in the mirror: an analysis of gothic aesthetics in the movie The Others (2001) through the Freudian concept of the Uncanny
Keywords: Os outros; Amenábar; Gótico; Infamiliar; Freud; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA